"\\frac{\\partial^{2}z}{\\partial^{2}x^{2}} + \\frac{\\partial^{2}z}{\\partial x\\partial y} + \\frac{\\partial z}{\\partial y} -z = e^{-x}"
Equation can be written as:
"(D^{2} + DD' + D' - 1)z = e^{-x}"
"(D + 1)(D + D' -1)z = e^{-x}"
Comparing above equation with
"(D -m_1 D' - \\alpha_1)(D -m_2 D' - \\alpha_2) = F(x,y)"
so "m_1 = 0, m_2 = -1, \\alpha_1 = -1, \\alpha_2 = 2"
So C.F. of the equation is
"C.F. = e^{-x}\\phi_1(y) + e^{x}\\phi_2(y-x)"
then PI is calculated as
"P.I. = \\frac{1}{(D+1)(D+D'-1)}e^{-x} = \\frac{1}{(D+1)(D-1)}e^{-x}" as exponential has no y.
"P.I. = \\frac{1}{(D+1)(D-1)}e^{-x}" "= e^{-x} \\frac{1}{D(D-2)}1" "= -\\frac{xe^{-x}}{2}"
So solution to the problem is
"z(x,y) = e^{-x}\\phi_1(y) + e^{x}\\phi_2(y-x) - \\frac{xe^{-x}}{2}"
Solution can be verified by taking partial derivatives and put them in differential equation.
Comments
Leave a comment